A physical approach for the estimation of the SERS enhancement factor through the enrichment and separation of target molecules using magnetic adsorbents. Issue 34 (27th May 2020) - Zhao, Danhui; Lin, Kui; Wang, Lanhui; Qiu, Zhigang; Zhao, Xin; Du, Kunze; Han, Lifeng; Tian, Fei; Chang, Yanxu
Abstract : The controllable synthesis of nanosized Fe3 O4 (10–20 nm) encapsulated in different numbers of graphene layers (1–5 layers) (Fe3 O4 @DGL NPs) was realized through a facile and green hydrothermal reaction at a temperature as low as 200 °C. Abstract : The controllable synthesis of nanosized Fe3 O4 (10–20 nm) encapsulated in different numbers of graphene layers (1–5 layers) (Fe3 O4 @DGL NPs) was realized through a facile and green hydrothermal reaction at a temperature as low as 200 °C. The competitive reduction–oxidation between reducing ethylene glycol (EG) and oxidizing H2 O under hydrothermal conditions resulted in the emergence of a magnetic Fe3 O4 core. Then, the pyrolytic reaction of the polyvinyl alcohol (PVA) molecules attached to the surface of the Fe3 O4 core with different surface densities led to the formation of graphene with a controlled number of layers. These Fe3 O4 @DGL NPs exhibited fast adsorption and sensitive SERS detection for rhodamine B (RhB). A physical and mathematical model was proposed for the estimation of the enhancement factor (EF) by combining the adsorption efficiency and SERS of RhB. This approach and model are applicable for the adsorption, sensitive SERS detection and determination of SERS EF when using functional magnetic nanoparticles as the adsorbent. The Fe3 O4 @1G NPs were also used as a novel nano-adsorbent for the fast removal of Escherichia coli ( E. coli ) from an aqueous solution. The Fe3 O4 @1G NPs regenerated after 3 cycles also showed high efficiency in the adsorption and separation of RhB and E. coli .